Multilingual science: discussing language as a place of encounter in knowledge production and exchange - Suzina Ana Cristina (Online Media and Global Communication)
Several recent studies collected evidence that demonstrates a linguistic disadvantage negatively affecting publication records of scholars using English as an additional language. This article frames these issues from three complementary perspectives, that are: a decolonial perspective, a perspective on disruptive capacity, and a participatory perspective. This systematization, based on literature review, allows to summarize a certain number of problems raised by previous studies and claims a shift from discrimination to domination debates. This posture still recognizes prejudices embedded in the publishing dynamics, but highlights that the latter can only exist in a system where science is perverted by commodified productive objectives. The present systematization also supports a solution that puts the multilingualism as a milestone sufficiently flexible to include different stages of progress in intercultural translation, while keeping high standards of academic production on the horizon. In a multilingual system, a collective mindset, intercultural translation, and a reviewed understanding of academic literacy recover the objectives of academic publishing as making science advance for the benefit of living conditions. This review sheds light on necessary changes that need to be implemented by funding agencies, publishing organizations, editors, peer-reviewers, authors and readers collectively. It demonstrates that making academic publication fairer to English as second language scholars will make it equally more meaningful for the whole society.